Extending illumination using all multiples: application to 3D acquisition geometry analysis. (13th October 2015) - Kumar, Amarjeet; Blacquière, Gerrit; Verschuur, Eric
Abstract : Recent advances in survey design have led to conventional common‐midpoint‐based analysis being replaced by subsurface‐based seismic acquisition analysis, with emphasis on advanced techniques of illumination analysis. Among them is the so‐called focal beam method, which is a wave‐equation‐based seismic illumination analysis method. The objective of the focal beam method is to provide a quantitative insight into the combined influence of acquisition geometry, overburden structure, and migration operators on the resolution and angle‐dependent amplitude fidelity of the image. The method distinguishes between illumination and sensing capability of a particular acquisition geometry by computing the focal source beam and the focal detector beam, respectively. Sensing is related to the detection properties of a detector configuration, whereas illumination is related to the emission properties of a source configuration. The focal source beam analyses the incident wavefield at a specific subsurface grid point from all available sources, whereas the focal detector beam analyses the sensing wavefield reaching at the detector locations from the same subsurface grid point. In the past, this method could only address illumination by primary reflections. In this paper, we will extend the concept of the focal beam method to incorporate the illumination due to the surface and internal multiples. This in fact complies with the trend of including multiples in the imaging process. Multiple reflections can illuminate a target location from other angles compared with primary reflections, resulting in a higher resolution and an improved illumination. We demonstrate how an acquisition‐related footprint can be corrected using both the surface and the internal multiples.